Ingress and egress motion strategies of elderly and young passengers for the rear seat of minivans with sliding doors. (March 2016) - Lu, Jun-Ming; Tada, Mitsunori; Endo, Yui; Mochimaru, Masaaki
Abstract: This study investigates the motion strategies performed by elderly and young passengers while entering and exiting the rear seat of minivans with sliding doors. A minivan mock-up was constructed with four adjustable parameters to represent nine different conditions of vehicle geometry. Ten elderly male participants (66.8 ± 3.8 years old) and ten young male participants (31.5 ± 6.6 years old) were recruited. Each of them entered and exited the minivan mock-up for five times under each condition, and the motion data were acquired by the optical motion capture system. Based on the criteria derived from previous studies, all motions were automatically categorized into seven ingress motion strategies and seven egress motion strategies. Further, the differences among motion strategies are discussed in terms of vehicle factors and passenger factors, which provide clues for future studies. Highlights: A quick method was proposed to identify ingress and egress motion strategies. Elderly and young passengers differed in their preference of ingress strategies. Elderly and young passengers had similar preference of egress strategies. The motion strategies seem to be not car dimension dominant but passenger dominant. The motion strategies requiring less exertion tend to be adopted more frequently.